2016
DOI: 10.1249/mss.0000000000000801
|View full text |Cite
|
Sign up to set email alerts
|

Tear Fluid SIgA as a Noninvasive Biomarker of Mucosal Immunity and Common Cold Risk

Abstract: Tear SIgA has utility as a noninvasive biomarker of mucosal immunity and common-cold risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 38 publications
6
49
0
Order By: Relevance
“…Modest dehydration as a result of heavy training or competition in the heat (typically of the order of 1-4% body mass loss) has been under the spotlight recently in exercise immunology and exercise physiology. [45][46][47] These recent exercise immunology findings harmonize with those from current research in exercise physiology that challenge the widely held belief that modest dehydration decreases exercise performance in the heat. 43 Although recent evidence indicates that modest dehydration may transiently decrease mucosal immunity, 44 the overwhelming balance of evidence suggests that modest dehydration typically experienced by athletes has relatively limited impact on exercise immune responses ( Table 2).…”
Section: Thermal Stress and Immunitysupporting
confidence: 56%
See 1 more Smart Citation
“…Modest dehydration as a result of heavy training or competition in the heat (typically of the order of 1-4% body mass loss) has been under the spotlight recently in exercise immunology and exercise physiology. [45][46][47] These recent exercise immunology findings harmonize with those from current research in exercise physiology that challenge the widely held belief that modest dehydration decreases exercise performance in the heat. 43 Although recent evidence indicates that modest dehydration may transiently decrease mucosal immunity, 44 the overwhelming balance of evidence suggests that modest dehydration typically experienced by athletes has relatively limited impact on exercise immune responses ( Table 2).…”
Section: Thermal Stress and Immunitysupporting
confidence: 56%
“…7 It is worth noting that individuals exercising in hot (vs cool) conditions tend to fatigue sooner or reduce their work rate so their exposure to exercise stress in the heat tends to be self-limiting. [45][46][47] For example, very recent research shows that modest dehydration (~4% body mass loss) caused by fluid restriction and prolonged moderate-intensity exercise did not affect circulating antigen-stimulated cytokine production, tear fluid IgA or saliva antimicrobial responses, including IgA, lysozyme and lactoferrin. The belief held by some exercise immunologists is that dehydration may impair immune health of athletes as dehydration increases physiological strain and immunomodulatory stress hormones.…”
Section: Thermal Stress and Immunitymentioning
confidence: 99%
“…Exercise immunology research (epidemiological and experimental) has grown substantially over the last few decades to investigate the relationship between exercise and URTI in humans (Shepard, 2010). In contrast to animal research, human studies (attempting to discern the effects of prolonged exercise/intense training on URTI) have mainly involved monitoring athletes following heavy exertion (i.e., relied on natural exposure to pathogens) but only a limited number of these have verified that symptoms are due to infectious agents (pathogens) (Spence et al, 2007;Schwellnus et al, 2010;Hanstock et al, 2016). This has raised concerns regarding the validity of URTI episodes (i.e., self-reported) in athletes that occur in and around competition or heavy periods of training (Bermon, 2007;Walsh et al, 2011b).…”
Section: Effects With Strenuous Training/in Athletesmentioning
confidence: 99%
“…Thus, the immunological profile of the tear fluid likely plays an important role in host defence against URTI, and moreover provides a non-invasive medium for assessment of immune status. We recently demonstrated that tear secretory IgA (SIgA) has potential as a biomarker of URTI risk (2) . It is likely that several other antimicrobial proteins abundant in tears such as lactoferrin (Lf) and lysozyme (Lys) contribute to host defence at the ocular surface (3) .…”
Section: Research In Sport and Physical Activity Annals Of Potential mentioning
confidence: 99%
“…To explore the potential of tear Lf and Lys to evaluate risk of subsequent URTI independently and in combination with tear SIgA data from the same subjects presented in Hanstock et al (2) .…”
Section: Purposementioning
confidence: 99%